Negations of the Laweyan Batik Community during the Pajang and Mataram Period - Hieronymus Purwanta; Victor Novianto (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: This study examines the negation of the Laweyan batik community during the Pajang and Mataram periods. It addresses two questions: why the Laweyan batik industry was negated and how such negation was expressed. The research employs the historical method, including source collection, source criticism, interpretation, and historiography, and uses Ernst E. Boesch’s symbolic action approach to analyze the intentions, procedures, goals, and situational context of historical actors. The findings show that the negation of the Laweyan batik community was closely related to the inability of Laweyan batik entrepreneurs to maintain harmonious relations with political authorities after the era of Ki Ageng Henis. This negation appeared in two main forms. First, it was expressed in folklore derived from traditional historiography, which portrayed Laweyan as socially improper, unlucky, and morally suspect. Second, it was reflected in rulers’ policies, particularly the tomb politics surrounding Ki Ageng Henis in Kotagede and the promotion of Kauman batik as a palace-centered alternative. These policies symbolically distanced royal authority from the commercial batik tradition associated with Laweyan. This study argues that the negation of Laweyan was not merely cultural prejudice, but also a political and symbolic strategy to preserve aristocratic identity and authority. It contributes to the socio-cultural history of batik by showing how power, memory, and symbolism shaped the historical marginalization of a local craft community. Abstrak: Kajian ini menganalisis penegasian terhadap komunitas batik Laweyan pada masa Pajang dan Mataram. Penelitian ini menjawab dua pertanyaan, yaitu mengapa industri batik Laweyan mengalami penegasian dan bagaimana bentuk-bentuk penegasian tersebut direpresentasikan. Penelitian menggunakan metode sejarah yang meliputi pengumpulan sumber, kritik sumber, interpretasi, dan historiografi. Analisis dilakukan dengan pendekatan tindakan simbolik Ernst E. Boesch untuk mengkaji intensi, prosedur, tujuan, dan keterlekatan situasional para aktor sejarah. Hasil penelitian menunjukkan bahwa penegasian terhadap komunitas batik Laweyan berkaitan erat dengan ketidakmampuan para pengusaha batik Laweyan menjalin hubungan harmonis dengan penguasa setelah masa Ki Ageng Henis. Penegasian tersebut hadir dalam dua bentuk utama. Pertama, melalui folklor yang bersumber dari historiografi tradisional dan menggambarkan Laweyan sebagai ruang sosial yang buruk, sial, dan tidak ideal. Kedua, melalui kebijakan penguasa, terutama politik makam terhadap Ki Ageng Henis di Kotagede dan pengembangan batik Kauman sebagai alternatif yang berorientasi istana. Kebijakan-kebijakan tersebut menjadi strategi simbolik untuk mengambil jarak dari tradisi batik komersial yang berkembang di Laweyan. Kajian ini menegaskan bahwa penegasian terhadap Laweyan bukan semata-mata prasangka kultural, melainkan juga strategi politik dan simbolik untuk menjaga identitas serta otoritas aristokrat. Studi ini berkontribusi pada sejarah sosial-budaya batik dengan menunjukkan bagaimana kuasa, memori, dan simbolisme membentuk marginalisasi historis terhadap komunitas perajin lokal.